Human rights indicators : a guide to measurement and implementation. (United Nations Human Rights, Office of the High Commissioner, 2012)
"The basic structure of the Guide is geared towards supporting a systematic and comprehensive translation of universal human rights standards into indicators that are contextually relevant. This approach favours using objective information which is easily available, or can be collected, for monitoring the national implementation of human rights. This requires the reader to: [1] Understand the conceptual approach so as to identify indicators, after developing a preliminary understanding of the human rights normative framework; [2] Explore the alternative data-generating methods to populate the selected indicators; and [3] Apply and interpret the numbers that go with an indicator so as to build an assessment on the state of human rights."--Page 8